Sterol Biosynthesis and Phytosterol Bioconversion in Crassostrea Gigas Larvae - Da Costa, Fiz; Mathieu-resuge, Margaux; Le Grand, Fabienne; Quéré, Claudie; Markov, Gabriel V.; Wikfors, Gary H.; Soudant, Philippe (Elsevier BV, 2024)
Highlights• A mass-balance approach compared dietary and larval sterol compositions.• Pacific oyster larvae synthetized de novo sterols under low dietary sterol supply.• Larval sterol biosynthesis was modulated by sterol dietary supply.• Dietary sterols were bioconverted under all dietary conditions.